An analysis of a 3-D finite element model of reinforced concrete (RC) beam upon treament of cracks / Mohd Zafri Mohd Ridzwan - Mohd Ridzwan, Mohd Zafri (Faculty of Civil Engineering, 2006)
Cracks are common phenomenon to concrete structures. The initial cause of cracking in concrete is due to shrinkage during setting. Cracks contribute to the deterioration of residual strength to concrete members. The applications of treatment are often required to rehabilitate the affected area. The aim of this study is to analyse reinforced concrete (RC) beam upon treatment of cracks, using Finite Element Method (FEM). A beam was modelled in 3-D solid using LUSAS version 13.6 sortware. The study considered all flexural, shear and cracking behaviour of the RC beam.